2015
DOI: 10.3892/mco.2015.617
|View full text |Cite
|
Sign up to set email alerts
|

Flap endonuclease 1 polymorphisms (rs174538 and rs4246215) contribute to an increased cancer risk: Evidence from a meta-analysis

Abstract: Abstract. Flap endonuclease-1 (FEN1) is a key factor during the maintenance of genomic stability and protection against tumorigenesis. Since the identification of functional polymorphisms of FEN1 (rs174538 and rs4246215), numerous studies have evaluated the association between the two single-nucleotide polymorphisms and cancer risk. To derive a more precise estimation, a meta-analysis was performed on the association between the FEN1 polymorphisms (rs174538 and rs4246215) and cancer risk. Odds ratios (ORs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Previous studies have shown that the FEN1 rs174538G>A SNP located in the promoter region causes increased promoter activity. These findings indicate that naturally occurring genetic polymorphisms in the regulation regions of cancer‐related genes may represent a significant potential factor for cancer risk . These results are also consistent with findings in hepatocellular carcinoma, and breast, lung, esophageal, gastric, and colorectal cancers in centers across China …”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that the FEN1 rs174538G>A SNP located in the promoter region causes increased promoter activity. These findings indicate that naturally occurring genetic polymorphisms in the regulation regions of cancer‐related genes may represent a significant potential factor for cancer risk . These results are also consistent with findings in hepatocellular carcinoma, and breast, lung, esophageal, gastric, and colorectal cancers in centers across China …”
Section: Discussionsupporting
confidence: 87%
“…The findings revealed that subjects with -69A or +4150T alleles of the FEN1 gene were associated with a decreased risk of cancer. A recent meta-analysis designated that FEN1 rs174538 and rs4246215 polymorphisms may contribute to an increased risk of cancer (28). The findings indicated that the GG or GA genotype increased the risk of cancer when compared to the rs174538 AA genotype.…”
Section: Discussionmentioning
confidence: 72%
“…Association study with 1840 lung cancer patients and 1958 controls further revealed that these two FEN1 SNPs conferred genetic susceptibility to lung cancer [ 49 ]. Moreover, some evidence was further observed to consolidate the contribution of the rs174538 and rs4246215 to the risk of different types of cancer [ 25 , 36 , 37 , 39 ]. Especially, these two SNPs were shown to decrease breast cancer risk in Chinese [ 25 ]and Iran [ 37 ] populations.…”
Section: Discussionmentioning
confidence: 99%